Evaluation of Community Knowledge Regarding Preparedness in Facing the Risk of Rob Flood Disaster in the Coastal Area of Dusun II Tanjung Rejo Village - Mutiara, Yusnidar Sari; Mrp, Mimbi Gusrera; Lea, Salshabila April; Moely, Cut Mulyana; Susilawati, Susilawati (Universitas Ibn Khaldun Bogor, 2025)
Tidal floods are one of the natural disasters that are increasingly occurring in Indonesia's coastal areas due to rising sea levels and climate change. Hamlet II, Tanjung Rejo Village, which is in the lowlands, is one of the areas that is vulnerable to tidal floods. This study aims to evaluate the level of community knowledge regarding preparedness in facing the risk of tidal floods. The methods used include pre-conditioning, education, discussion and evaluation stages. The results of the activity showed a significant increase in community knowledge after the socialization was carried out. Before the socialization, only 14 out of 50 respondents understood preparedness steps, but this number increased to 43 respondents after the activity took place. This increase indicates that education and outreach programs are effective in increasing public awareness of preparedness for tidal floods.